The Influence Of Service Quality And Marketing Mix On Customer Satisfaction - Gama, Jaya Adi; Putri, Safira Rifnu; Kuat Prabowo, Pancanto (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2024)
The aim of this research is to be able to analyze and determine (1) the influence of promotions on customer satisfaction, (2) the influence of service quality on customer satisfaction, (3) the influence of product quality on customer satisfaction, (4) the influence of promotion quality, service quality and product quality on customer satisfaction. . This research is survey research. The population in this research is consumers of the Arcana audio sound system shop in the Sukodono area. The sample size for this survey was 38 respondents. The sampling method uses a deliberate sampling technique, namely determining the sample based on certain considerations. The data collection technique uses a questionnaire by giving respondents a list of statements. This research uses multiple linear regression tools using the SPSS 23.0 for Windows program. Based on the results of data analysis, we found that product quality collectively has a positive and significant influence on customer satisfaction. This can be seen from the ttug value of 5.518 > ttable 2.034 and the significance value of 0.000 < 0.05. Meanwhile, promotion and product quality, on the other hand, do not affect customer satisfaction. The F test results showed that the Fcount value was 16.494 > Ftable 2.88 and the significance value was 0.000 < 0.05. From this, it can be concluded that together promotional variables, service quality and product quality have a positive and significant influence on customer satisfaction. From the results of the analysis, a coefficient of determination (R2) score of 0.593 can be obtained. This means that the three variables of promotion, service quality and product quality together contribute 59.3% to customer satisfaction.